KETERKAITAN DISPOSISI MATEMATIS DENGAN PRESTASI BELAJAR MATEMATIKA SISWA SEKOLAH MENENGAH PERTAMA - Halini, Halini; Pasaribu, Revi Lestari; Zubaidah, Zubaidah (Universitas Tanjungpura, 2023)
Mathematical disposition is one of the main factors in determining mathematics learning achievement in students, and mathematical disposition is believed to support the success of learning mathematics significantly. So it is necessary to research the relationship between mathematical dispositions and mathematics learning achievement in students. This study aims to: 1) describe the mathematical disposition of junior high school students, 2) describe the mathematics learning achievement of junior high school students, and 3) empirically test the relationship between mathematical dispositions and mathematics learning achievement of junior high school students. The research was conducted with a quantitative approach. The instrument used in this study was a mathematical disposition scale test, and the results of the mid-semester test. This study involved 572 junior high school students in grades VII and VIII in the Pontianak area. The data obtained will be analyzed using correlation analysis between disposition and learning achievement in mathematics. The results showed: 1) Most junior high school students had moderate and low levels of mathematical disposition, 2) Most junior high school students had moderate, low, and meager mathematics learning achievements, 3) there was a relationship between mathematical disposition and learning achievement. Based on the results of the research, it is recommended that mathematics teachers be able to develop aspects related to student psychology through a strategic mathematical learning process in the classroom.